Penerapan Terapi Rendam Kaki dengan Air Hangat terhadap Tekanan Darah pada Pasien Gagal Ginjal Kronis - Nurlailika; Sulistiowati, Sri (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
Kidney failure is a significant cause of death with around 697.5 million cases and has become the 12th leading cause of death worldwide. Chronic kidney failure is closely related to hypertension because it is one of the complications of kidney failure. Increased blood pressure in chronic kidney failure patients who are not treated properly will cause further complications. Therefore, hypertension in patients with chronic kidney failure must be anticipated immediately, one of which is warm water foot soak therapy. Objective : To know the description of foot soak therapy with warm water on blood pressure in patients with chronic kidney failure in the Hemodialysis Room of Cibinong Hospital. Methods: The research method used was a case study with the application of evidence-based interventions or evidencebased practice, with 2 patients who had a history of hypertension and when their blood pressure was measured more or equal to 140/90 mmHg. The instruments used were a manual sphymomanometer and stethoscope, observation sheets and standard operating procedures. Results: Based on the results of the intervention of applying warm water foot soak therapy in patients with chronic kidney failure, it can be concluded that the blood pressure value in patient 1 before the intervention was 190/100 mmHg. Whereas in patient 2 before the intervention, it was 170/90 mmHg. After the intervention was carried out for 3 days in both patients, it was found that the blood pressure value in patient 1 was 150/80 mmHg. Whereas in patient 2 it became 140/80 mmHg. Conclusion: The conclusion of this study is that there are changes in systolic and diastolic pressure in both patients before and after the foot soak intervention with warm water